Aerosol mass scattering efficiencies and single scattering albedo under high mass loading in Chiang Mai valley, Thailand - Shantanu Kumar Pani; Lin, Neng Huei; Wang, Sheng Hsiang; Somporn Chantara; Stephen M. Griffith; Chang, Jackson Hian-Wui (Elsevier Ltd, 2023)
Aerosols amend the Earth's radiation budget by absorbing and scattering the incoming solar radiation. Severe air pollution episodes with high aerosol loading have continually occurred in northern Thailand for a long decade. This study comprehensively investigates the light scattering mechanism contingent on synchronous measurement of aerosol physicochemical and optical properties at Chiang Mai, the second largest city in Thailand per population, for two months during the spring of 2016. Daily mean values of the aerosol light scattering coefficient (σsca) at 550 nm ranged between 146 and 501 Mm−1. The scattering Ångström exponent (SAE450/700) ranged from 1.7 to 2.1, indicating a predominant contribution of finer particles to total light scattering. The mean mass scattering efficiency (MSE) of (NH4)2SO4, NH4NO3, organic matter (OM), dust, and others at 550 nm, estimated using a multilinear regression model were 3.3, 1.4, 4.4, 1.8, and 4.0 m2 g−1, respectively. The mean contribution of individual components to σsca was in the order of OM (66%) > Others (12%) > Dust (11%) > (NH4)2SO4 (9%) > NH4NO3 (2%). The mean (±SD) value of aerosol single scattering albedo at 550 nm wavelength was 0.80 ± 0.02 (range; 0.75–0.84), highlighting the presence of strongly absorbing aerosols. The total light absorption was primarily due to the mixture of organic and elemental carbons. The mean (±SD) MSE and mass absorption efficiency (MAE) of composite aerosols were 3.4 ± 0.4 m2 g−1 and 0.9 ± 0.1 m2 g−1, respectively. Notwithstanding the absorption, a simple radiative transfer model quantifies a negative top-of-atmosphere radiative forcing over Chiang Mai. These findings shed light on the impact of ambient aerosols on light scattering and urban climate. Moreover, our study offers a basic dataset to assess the visibility impairment in Chiang Mai.